PERSEPSI PERAWAT TENTANG JENJANG KARIR: STUDI MIX METHOD - Saputri, Ekawati; Nasus, Evodius (Jurnal Keperawatan Malang, 2024)
Background: A nurse career ladder program encourages and nurtures the development and professional practice of nurses. The implementation of career ladder has also been implemented by one of the state hospitals in Southeast Sulawesi Province. The majority of nurses in the hospital have had careers as clinical nurses (CN) with different career levels and status as State Civil Apparatus or ASN. Career development of nurses is only based on class/rank increases by the status of nurses as ASN and competency improvement only according to needs and nurses continue formal education to increase class/rank. Objective:  To analyze nurses' perceptions of the career ladder with a mixed-method study approach. Methods: Mixed method research with a sequential explanatory model approach that combines quantitative research with descriptive analysis and qualitative with in-depth interviews. The sample size was 90 people using a purposive sampling technique with inclusion criteria willing to be respondents and not on leave and 7 respondents for in-depth interviews. Data analysis with univariate tests and interview transcripts by determining themes. Results:  Nurses perceived a good career ladder by 44.4% and unfavorable by 55.6%. Career ladders have been implemented through credentialing tests every year.  The promotion system is still based on employee rank. Nurses have obtained clinical assignment letters but have not carried them according to their clinical level. Rewards in the form of incentives are perceived well by nurses and are received differently depending on the level of education.  Implication: Nurses’ career ladder can improve nurses’ competence through career level increases.